Social Media as a Product Promotion Tool for The Parish of Santo Thomas Rasul Bedono MSME Community - Bernadeta Lenny Setyowati; Bayu Widiantoro (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2024)
The aim of this community service was to activate the parish of St. Thomas Rasul Bedono Micro, Small, and Medium Enterprises (MSME) community, which was already exist at that time, but it was not fully developed. The purpose of this community service was to share knowledge about the use of social media as a promotional tool for the mentioned MSME community. The MSME product images on their website were too simple. A product depends not only on the quality of the product itself, but also on how the photo of the product is presented on both websites and social media. Poor photo techniques will have an impact on the product's appeal, resulting in an impact on the sale of the product. The method for each activity in the community service program includes literacy, practice applying copywriting to social media uploads, practice on photography. Outcome of this community service was the application of social media as a promotional medium with application of copywriting to its upload and photography training utilizing mobile phones to support the promotional effort. The community service team was also helped the MSME actors in the mentioned community who were not yet actively involved, by means of interviewing them, writing articles about their businesses, and then publishing the articles on the parish MSME community website. The impact of this community service was an increase in the ability of the MSME actors to promote their products by uploading attractive product photos and applying copywriting concepts through social media, thus encouraging consumers to purchase, expanding the market, and increasing their income.